Fate and Effects of Oil Pollutants in Extremely Cold Marine Environments. - Atlas, Ronald M (1977)
Petroleum degradation was studied using Prudhoe Bay crude oil incubated in situ in several Arctic ecosystems. Studies were conducted in water, ice and sediment ecosystems. No biodegradation of oil was found when oil was allowed to freeze into the ice matrix. When oil was spilled under ice evaporative losses were greatly restricted and biodegradation rates were very low. In sediment, biodegradative changes in the oil were found within a few days of spillage. When sediment was contaminated with oil there was extensive mortality of invertebrates. Recolonization of contaminated sediment occurred rapidly but recolonization was by different benthic invertebrate species than recolonized uncontaminated sediment.